2009
DOI: 10.1021/ol900433g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Self-Immolation: Faster Signal Relay over a Longer Linear Distance?

Abstract: A counterintuitive observation of a faster signal relay over a longer linear distance prompted detailed kinetic studies of self-immolation reactions. With appropriate conformational bias, trigger-to-reporter signal transduction can take an efficient "shortcut" that outperforms conventional pathways involving repetitive quinone methide rearrangements and elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
2
32
0
6
Order By: Relevance
“…Indeed, half-times larger by several order of magnitudes (> 10 3 times) [52] have been observed for spacers where the leaving group was linked by an ether (formulas 38 and 42;F igure 7) with respect to analogous spacers in which the leaving group was bound by ac arbonate (formulas 39 and 40)o rc arbamate (formula 41). [52,53] Indeed the carboxylate group is am uch better leaving group than the alcoholate group.I nf act, the decarboxylation of the carbamic acid may even become rate-limiting in the whole disassembly process:Decarboxylation half-times in the 5min range have been reported at 293 K [53,124] Furthermore,r eporters directly linked to the benzylic position through an amine or thiol bond lead to almost no liberation except under rather drastic experimental conditions or specific aromatic substitutions (formulas [27][28][29][30]. [79,90,120] As expected from the stabilization of the partial positive charge at the benzylic position in the transition state,t he introduction of am ethyl substituent at the benzylic substituent was also shown to significantly accelerate the elimination of the quinone methide intermediate (compare formulas 44 and 46 with formulas 43 and 45).…”
Section: Linking Core Leaving Groups and Substituents At The Benzylicmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, half-times larger by several order of magnitudes (> 10 3 times) [52] have been observed for spacers where the leaving group was linked by an ether (formulas 38 and 42;F igure 7) with respect to analogous spacers in which the leaving group was bound by ac arbonate (formulas 39 and 40)o rc arbamate (formula 41). [52,53] Indeed the carboxylate group is am uch better leaving group than the alcoholate group.I nf act, the decarboxylation of the carbamic acid may even become rate-limiting in the whole disassembly process:Decarboxylation half-times in the 5min range have been reported at 293 K [53,124] Furthermore,r eporters directly linked to the benzylic position through an amine or thiol bond lead to almost no liberation except under rather drastic experimental conditions or specific aromatic substitutions (formulas [27][28][29][30]. [79,90,120] As expected from the stabilization of the partial positive charge at the benzylic position in the transition state,t he introduction of am ethyl substituent at the benzylic substituent was also shown to significantly accelerate the elimination of the quinone methide intermediate (compare formulas 44 and 46 with formulas 43 and 45).…”
Section: Linking Core Leaving Groups and Substituents At The Benzylicmentioning
confidence: 96%
“…a) 1,4-elimination; [52][53][54]71] b) 1,6-elimination; [52,54,55,71] c),d) 1,8elimination. Theo ther key factor Figure 2.…”
Section: Self-immolation:amultistep Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon examination of the solution stability of these compounds, 3 and 4 were stable in buffer over a 24 h time period, while 5 showed > 50% hydrolysis ( Figure S6). Although the use of carbonate and carbamate ester linkages in self-immolative systems are more common (due to the additional thermodynamic driving force from the release of CO 2 in the cascade reaction), [21,22] our findings suggest that the carbonate ester linkage was not optimal because of the low aqueous stability observed for 5. In addition, we found that incorporation of the carbonate ester linkage was synthetically more challenging and less reliable (i.e.…”
mentioning
confidence: 71%
“…Carbonate and carbamate linkages are much more common in the literature due to the thermodynamic driving force of the release of CO 2 in the elimination reaction, leading to fast rates of reaction. [19] Studies on our boronic ester-benzyl ether linkage indicated superior aqueous stability to that of the corresponding carbonate ester, with similar cleavage kinetics. [20] Our initial studies have led to the development of biocompatible polymeric nanoparticles that undergo desired cargo release in response to H 2 O 2 [21] as well as new H 2 O 2 activated prochelators.…”
Section: Introductionmentioning
confidence: 99%